Analisis Pengaruh Inflasi dan CAR terhadap Pembiayaan Murabahah pada PT Bank Aceh Syariah - Humaira, Rafiqah (Universitas Islam Islam Sumatera Utara, 2024)
This research aims to analyze the influence of Inflation and Capital Adequacy Ratio (CAR) on Murabahah Financing at PT Bank Aceh Syariah. The data used is Time Series data for the period September 2011 – June 2018 with a quantitative linear regression analysis method. The results of the discussion show that the Inflation variable is partially insignificant and has a negative relationship to distributed Murabahah Financing, while the CAR variable is partially significant and has a positive relationship to distributed Murabahah Financing. However, inflation and CAR simultaneously have a significant effect and are positively related to distributed Murabahah financing. These two independent variables are able to explain the dependent variable by 51.6% of the Adjusted R Square value and the remaining 48.4% is influenced by other variables.